The nuclear factor kappa B signaling pathway is a master regulator of renal fibrosis - Ren, Na; Wang, Wen-Feng; Zou, Liang; Zhao, Yan-Long; Miao, Hua; Zhao, Ying-Yong (Frontiers in Pharmacology, 2024)
Renal fibrosis is increasingly recognized as a global public health problem. Acute kidney injury (AKI) and chronic kidney disease (CKD) both result in renal fibrosis. Oxidative stress and inflammation play central roles in progressive renal fibrosis. Oxidative stress and inflammation are closely linked and form a vicious cycle in which oxidative stress induces inflammation through various molecular mechanisms. Ample evidence has indicated that a hyperactive nuclear factor kappa B (NF-ƙB) signaling pathway plays a pivotal role in renal fibrosis. Hyperactive NF-ƙB causes the activation and recruitment of immune cells. Inflammation, in turn, triggers oxidative stress through the production of reactive oxygen species and nitrogen species by activating leukocytes and resident cells. These events mediate organ injury through apoptosis, necrosis and fibrosis. Therefore, developing a strategy to target the NF-ƙB signaling pathway is important for the effective treatment of renal fibrosis. This review summarizes the effect of the NF-ƙB signaling pathway on renal fibrosis in the context of AKI and CKD (immunoglobulin A nephropathy, membranous nephropathy, diabetic nephropathy, hypertensive nephropathy and kidney transplantation). Therapies targeting the NF-ƙB signaling pathway, including natural products, are also discussed. In addition, NF-ƙB-dependent noncoding RNAs are involved in renal inflammation and fibrosis and are crucial targets in the development of effective treatments for kidney disease. This review provides a clear pathophysiological rationale and specific concept-driven therapeutic strategy for the treatment of renal fibrosis by targeting the NF-ƙB signaling pathway.